Citizen Participation in Local Government Services: ?zmir Metropolitan Municipality Example - Akyıldız, Fulya (European Journal of Multidisciplinary Studies, 2017)
The aim of this study is to demonstrate citizen participation in local government services in Turkey, for example in ?zmir Metropolitan Municipality. In accordance with the amendments made in the Municipal Law and the Special Provincial Administration Law in 2005, the Regulations published by the Ministry of Interior in 2006 opened the way for citizen participation in the execution of public services in local governments. Despite the past decade, citizen participation in local services is still in its infancy, with few exceptions today. Programs that include citizen participation in ?zmir Metropolitan Municipality which is one of these exceptions are analyzed with this study and it is presented as an example to other local administrations. A reason for the selection of a metropolitan municipality within the scope of the study is that the metropolitan municipalities of 30 provinces, which are metropolitan with an amendment made in Law No. 6360 in 2012, are responsible for providing services on the provincial property boundary. In spite of the increased service obligation and responsibility of the metropolitan municipalities, the cost of services has also increased, and at the extreme, it seems difficult to take local services effectively and efficiently. The study suggests that the metropolitan municipalities should make widespread use of this method in the welfare services that affect people’s daily life and quality of life. Citizen participation in services has a critical prescription for the success of local programs and for institutional performance. In the study, voluntary participation in local services is linked to the New Public Service (NPS) approach within the framework of democracy, citizen participation and democratic governance concepts. Among public service delivery and distribution methods is very important, and although the New Public Management approach is an alternative model to privatization practices, the citizen participation in public services has been underestimated in Turkey. This study aiming to fill this gap aims to attract the attention of the academic field to this topic and to give new ideas to the local politicians and practitioners. In this context, first of all, the issue of NPS approach and citizen participation in the services is discussed. Later, information on citizen participation in local government services in Turkey is given and the existing applications of the Izmir Metropolitan Municipality are examined. Following the presentation of the findings and suggestions, a general evaluation is made and the study is terminated.